Analisis Deskriptif Pencapaian Audit Mutu Internal Stikes Mitra Keluarga rentang 2019-2020 - Anung Ahadi Pradana; Lina Herida Pinem; Susi Hartati; Guntari Prasetya; Rohayati Rohayati; Elfira Maya Sari; Intan Kurnia Putri (UHN IGB Sugriwa Denpasar, 2022)
quality assurance system is one of the steps for higher education in improving the quality of the implementation of the Tridharma and services to the community as a form of Good University Governance. In implementing the internal quality assurance system, STIKes Mitra Keluarga has been implementing it since 2015 and always conducts analysis regularly every year. The type of research carried out is a descriptive analysis of the data from the implementation of the Internal Quality Audit (AMI) conducted by LPMI STIKes Mitra Keluarga in 2018/19 and 2019/20. The data obtained are then compared with the results between the items of conformity (KS) and non-compliance (KTS) from Education Standards, Research Standards, PKM Standards and Internal Driven Standards (Student Admission (PMB), Student Affairs, Graduates, Management Information Systems (SIM) and Cooperation). The results of the descriptive analysis carried out found an increase in the percentage of conformity (KS) and a decrease in the percentage of non-conformance (KTS) from the implementation of the Internal Quality Audit in 2018/19 and 2019/20. Several operational problems related to the implementation of the quality management system. Based on the results of the internal quality audit, several problems were found related to the implementation of the quality assurance system, including: 1) Not 100% of the STIKes Mitra academic community has a high awareness of quality commitment and performance documentation, 2) Auditees are not 100% obedient in the use of procedure manuals and still often replace documents without legal aspects from LPM, and 3) Efforts to achieve standards have not been carried out overall. The prevention strategies planned by STIKes Mitra Keluarga include: 1) Refreshing the quality commitment of the STIKes Mitra Keluarga academic community, 2) At the beginning of each semester, documents will be issued from the UPM of each study program and the frequency of monitoring and evaluation of the use of documents will be increased, 3) STIKes Mitra Keluarga leaders need to motivate the entire community to try to implement a strategy to achieve quality standards, 4) Make quality standards as indicators in strategic plans, and 5) Implement a system of rewards and punishments.